A positive electrode material, a preparation method thereof, a positive electrode sheet, and a lithium ion battery

CN119560520BActive Publication Date: 2026-10-23SHENZHEN HIGHPOWER TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411494808.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2026-10-23
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

[0003]本发明实施例提供一种正极材料及其制备方法、正极极片、锂离子电池,以解决三元正极材料容易反应及被腐蚀的问题,达到提高电池的稳定性和安全性的效果

Benefits of technology

本发明通过将Bi2SeO5包覆在三元材料LiNixM1-xO2上,能有效防止三元材料与电解液的接触,抑制高电压下的电解液的分解和界面副反应的发生,减少三元材料表面离子的溶解析出,提高正极活性材料的表面结构的稳定性。并且,高介电常数的Bi2SeO5可以在电池充放电过程中提供更有效的电场分布调控,减少电极材料的极化损耗,提高正极活性材料的倍率性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

This invention discloses a positive electrode material and its preparation method, a positive electrode sheet, and a lithium-ion battery. The positive electrode material includes a core and a shell covering the core, wherein the core comprises LiNi. x M 1‑ x O2; wherein M is selected from at least two elements chosen from Mn, Fe, Co, Ti, Y, Sc, Ru, Cu, Mo, Ce, W, Zr, Ca, and P, and 0.3 ≤ x < 1; the shell material is Bi2SeO5. This invention involves coating Bi2SeO5 onto a ternary material LiNi. x M 1‑x On O2, contact between the ternary material and the electrolyte can be effectively prevented, inhibiting electrolyte decomposition and interfacial side reactions under high voltage, reducing the dissolution and release of ions from the surface of the ternary material, and improving the stability of the surface structure of the positive electrode active material. Furthermore, the high dielectric constant of Bi2SeO5 material can provide more effective electric field distribution control during battery charging and discharging, reducing polarization losses of the electrode material and improving the rate performance of the positive electrode active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium batteries, and more particularly to a positive electrode material and its preparation method, a positive electrode sheet, and a lithium-ion battery. Background Technology

[0002] In the development of lithium-ion batteries, the choice of cathode material plays a crucial role in battery performance. Ternary materials (usually referring to composite oxides containing nickel, cobalt, and manganese) are considered one of the most promising cathode materials due to their high energy density, low cost, and excellent electrochemical performance. However, lithium-ion batteries using ternary materials are susceptible to interface corrosion by the electrolyte, leading to failure. This corrosion is mainly due to the active metal Ni in high-nickel ternary cathode materials. 4+ Harmful side reactions occur with carbonate electrolytes, leading to excessive deposition of byproducts at the cathode-electrolyte interface (CEI) and potentially triggering thermal runaway, thus affecting battery stability and safety. Furthermore, the interaction between traditional carbonate electrolytes and ternary materials promotes surface dissolution, resulting in the loss of active materials. Summary of the Invention

[0003] This invention provides a cathode material and its preparation method, a cathode sheet, and a lithium-ion battery to solve the problems of easy reaction and corrosion of ternary cathode materials, thereby improving the stability and safety of the battery.

[0004] Specifically, the present invention provides a cathode material comprising a core and a shell covering the core, wherein the core comprises LiNi. x M 1-x O2; wherein M is selected from at least two elements selected from Mn, Fe, Co, Ti, Y, Sc, Ru, Cu, Mo, Ce, W, Zr, Ca and P, and 0.3≤x<1; the shell material is Bi2SeO5.

[0005] Optionally, the thickness of the shell is 1 nm to 50 nm; And / or, the core and the shell are mutually doped at adjacent interfaces to form an intermediate layer, the thickness of which is 0.5 nm to 200 nm.

[0006] Optionally, the mass percentage of Bi2SeO5 in the cathode material is 0.05% to 5%.

[0007] Optionally, the Bi2SeO5 accounts for 0.1% to 2% of the mass of the cathode material.

[0008] Optionally, the median particle size D of the Bi2SeO5 50 The particle size is 1 nm to 5 μm; and the median particle size D of the Bi₂SeO₅ is...50 Smaller than the LiNi x M 1-x The median particle size D of O2 50 .

[0009] Optionally, the median particle size D of the Bi2SeO5 50 The range is 10nm to 500nm.

[0010] This invention also provides a method for preparing a cathode material, comprising the following steps: LiNi x M 1-x O2 material is mixed with Bi(NO3)3 material and selenium powder to obtain a mixed substance; The mixture is sintered under preset conditions to obtain the cathode material.

[0011] Optionally, the preset conditions include: the sintering is carried out in an atmosphere of oxygen or air; the sintering temperature is 300℃~700℃; and the sintering time is 3h~10h.

[0012] The present invention also provides a positive electrode sheet, comprising a current collector and an active layer, wherein the active layer is disposed on at least one side of the current collector, and the active layer comprises a positive electrode material as described in any of the preceding claims.

[0013] The present invention also provides a lithium-ion battery, including the above-described positive electrode sheet.

[0014] The beneficial effects of this invention are as follows: This invention involves coating Bi2SeO5 onto the ternary material LiNi. x M 1-x On O2, it can effectively prevent the contact between ternary materials and electrolyte, suppress electrolyte decomposition and interfacial side reactions under high voltage, reduce the dissolution and release of ions from the surface of ternary materials, and improve the stability of the surface structure of the positive electrode active material. Furthermore, the high dielectric constant of Bi2SeO5 can provide more effective electric field distribution control during battery charging and discharging, reduce polarization losses of electrode materials, and improve the rate performance of the positive electrode active material. Detailed Implementation

[0015] To make the technical problems solved, the technical solutions, and the beneficial effects of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.

[0016] This invention provides a cathode material comprising a core and a shell covering the core, wherein the core comprises LiNi containing lithium, M, and nickel. xM 1-x O2; wherein M is selected from at least two elements selected from Mn, Fe, Co, Ti, Y, Sc, Ru, Cu, Mo, Ce, W, Zr, Ca and P, and 0.3≤x<1; the shell material is Bi2SeO5.

[0017] In this embodiment of the invention, Bi2SeO5 is coated onto the ternary material LiNi. x M 1-x On O2, contact between the ternary material and the electrolyte can be effectively prevented, inhibiting electrolyte decomposition and interfacial side reactions under high voltage, reducing the dissolution and release of ions from the surface of the ternary material, and improving the stability of the surface structure of the positive electrode active material. Furthermore, the high dielectric constant of Bi2SeO5 material can provide more effective electric field distribution control during battery charging and discharging, reducing polarization losses of the electrode material and improving the rate performance of the positive electrode active material.

[0018] In one embodiment of the present invention, the thickness of the shell is 1 nm to 50 nm. If the thickness of the shell is too large, it will make LiNi... x M 1-x The reduced proportion of O2 material in the cathode material leads to a decrease in battery energy density. If the shell thickness is too small, the shell is thin and prone to cracking, making it difficult to effectively prevent contact between the ternary material and the electrolyte. The shell thickness can specifically be 1 nm, 3 nm, 9 nm, 15 nm, 20 nm, 25 nm, 30 nm, 40 nm, or 50 nm. Preferably, the shell thickness is 3 nm to 30 nm; more preferably, the shell thickness can be 3 nm to 20 nm. The diameter of the core is 2 μm to 20 μm. If the core diameter is too large, it is not conducive to the subsequent preparation of the cathode sheet; if the core diameter is too small, after coating with Bi2SeO5 material, the proportion of the core is relatively small, resulting in a decrease in battery energy density.

[0019] In one embodiment of the present invention, the Bi₂SeO₅ content in the cathode material is 0.05% to 5% by mass. Specifically, the Bi₂SeO₅ content in the cathode material is 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5% by mass. A small amount of Bi₂SeO₅ forms a structurally stable coating layer on the surface of the ternary material, which neither affects the dielectric properties of Bi₂SeO₅ nor the activity of the ternary material, thus enabling the active material to obtain excellent electrochemical performance. Preferably, the Bi₂SeO₅ material content in the cathode material is 0.1% to 2% by mass.

[0020] The present invention also provides a method for preparing a cathode material, used to prepare the cathode material in any of the above embodiments, the preparation method comprising the following steps: LiNi x M 1-x O2 is mixed with Bi(NO3)3 and selenium powder to obtain a mixed substance; The mixture is sintered under preset conditions to obtain the cathode material.

[0021] The process steps in this embodiment are simple and can quickly produce cathode materials coated with Bi2SeO5. While maintaining the surface structure stability of the cathode material, it improves the overall performance of the cathode material, so that when applied to lithium-ion batteries, the lithium-ion batteries have excellent electrochemical performance.

[0022] In one embodiment of the present invention, LiNi x M 1-x The median particle size D of O2 50 The median particle size D of Bi(NO3)3 is 2μm~20μm. 50 The size is 1nm~5μm, and it must meet the requirements of LiNi x M 1-x The median particle size D of O2 50 The median particle size is larger than that of Bi(NO3)3, so that the median particle size D of the generated Bi2SeO5 is larger. 50 Also smaller than LiNi x M 1-x The median particle size D of O2 50 This allows Bi₂SeO₅ to form a uniform and dense shell, more completely encapsulating the ternary material core. Furthermore, the particle size of Bi₂SeO₅ is smaller than that of the ternary material LiNi. x M 1-x The particle size of O2 allows small Bi2SeO5 particles to be more evenly dispersed between large ternary material particles, increasing the contact area between them, and thus allowing Bi2SeO5 to be more completely coated on the ternary material.

[0023] Preferably, LiNi x M 1-x The median particle size D of O2 50 The median particle size D of Bi₂SeO₅ ranges from 2 μm to 15 μm. 50 The thickness is 10 nm to 1 μm. More preferably, LiNi x M 1-x The median particle size D of O2 50 The median particle size D of Bi₂SeO₅ is 5μm~10μm. 50 The range is 10nm to 500nm.

[0024] In one embodiment of the present invention, the preset conditions include: the sintering is carried out in an atmosphere of oxygen or air to provide oxygen for the formation of Bi2SeO5; the sintering temperature is 300℃~700℃; and the sintering time is 3h~10h. During the sintering process, the precursor Bi(NO3)3 material and selenium powder form Bi2SeO5. During the sintering process, the contact surface between Bi2SeO5 and the ternary material forms a transition mixture, which can then form a core and shell distributed from the inside out. If the sintering temperature is too low or the sintering time is too short, it is difficult to form a structure in which the shell tightly covers the core; if the sintering temperature is too high or the sintering time is too long, it will cause the ternary material particles to regrow, resulting in larger particle sizes and more severe cation mixing in the crystal structure, thereby deteriorating the electrical performance of the cathode material.

[0025] Specifically, the sintering temperature is 300℃, 350℃, 400℃, 450℃, 500℃, 550℃, 600℃, 650℃ or 700℃; the sintering time is 3h, 4h, 5h, 6h, 7h, 8h, 9h or 10h.

[0026] One embodiment of this application also provides a positive electrode sheet, which includes a current collector and an active layer disposed on at least one side. The active layer comprises the positive electrode material of any of the above embodiments. The current collector can be a conventional metal foil or a composite current collector.

[0027] Specifically, the positive electrode material may also include conductive agents, binders, solvents, etc., which can be selected according to relevant technologies and are not limited thereto. Furthermore, the positive electrode sheet of this application can be prepared according to relevant technologies. For example, the positive electrode active material, conductive agent, binder, etc., in the above-mentioned positive electrode material are mixed evenly according to a preset mass ratio, an appropriate amount of solvent is added and ground to form a slurry, which is then coated onto a current collector. Through drying, cutting, and other processes, the positive electrode sheet is obtained.

[0028] One embodiment of this application also provides a lithium-ion battery, which includes a positive electrode, a separator, a negative electrode, and an electrolyte according to any of the above embodiments. The positive electrode, separator, and negative electrode can be fabricated into an electrode assembly using a winding process or a stacking process. The electrolyte can be selected from any electrolyte suitable for ternary lithium batteries in the prior art, and is not particularly limited thereto.

[0029] One embodiment of this application also provides an electronic device that includes the aforementioned lithium-ion battery. The lithium-ion battery serves as the power source for the electronic device and can also be used as an energy storage unit. The electronic device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0030] The present invention will be further illustrated by the following examples.

[0031] Example 1 (1) Weigh Bi(NO3)3, the precursor of Bi2SeO5, and selenium powder according to the molar ratio of Bi:Se 2:1, and add Bi(NO3)3 and selenium powder into a planetary ball mill for ball milling to obtain the first mixture.

[0032] (2) According to Bi2SeO5 and LiNi 0.8 Co 0.1 Mn 0.1 The theoretical mass ratio of O2 is 0.2:99.8. Weigh out the first mixture and the median particle size D respectively. 50 LiNi, a ternary material with a thickness of 9.3 μm 0.8 Co 0.1 Mn 0.1 O2, and mix the two evenly to obtain a second mixture.

[0033] (3) After sintering the first mixture at 500°C for 10 hours in an oxygen atmosphere, the sintered material is sieved to remove impurities generated by the saggar and other equipment used in the sintering process, and a positive electrode material with a Bi2SeO5 content of 0.2wt% is obtained.

[0034] (4) The positive electrode material, conductive agent CNT (carbon nanotubes), and binder PVDF (polyvinylidene fluoride) are thoroughly mixed in N-methylpyrrolidone solvent at a mass ratio of 97:1.5:1.5 to form a uniform positive electrode slurry. The positive electrode slurry is coated onto the positive electrode current collector aluminum foil. After drying and cold pressing, the positive electrode sheet is obtained.

[0035] (5) Preparation of negative electrode sheet The negative electrode active material (silicon-oxygen-carbon composite), conductive agent (acetylene black), binder (styrene-butadiene rubber), and thickener (sodium carboxymethyl cellulose) were thoroughly mixed in an appropriate amount of deionized water solvent at a mass ratio of 95:2:2:1 to form a uniform negative electrode slurry. The negative electrode slurry was then coated onto a copper foil current collector. After drying and cold pressing, the negative electrode sheet was obtained.

[0036] (6) Preparation of lithium-ion batteries The separator in this step is a porous PE polymer film, and the electrolyte is a carbonate-based electrolyte.

[0037] The positive electrode sheet, separator, and negative electrode sheet obtained in step (4) are stacked sequentially, with the separator positioned between the positive and negative electrodes for isolation. The stacked positive electrode sheet, separator, and negative electrode sheet are wound into a core. The core is placed into a pre-formed aluminum-plastic film bag and electrolyte is injected. After vacuum sealing, settling, and formation processes, a lithium-ion battery is obtained.

[0038] The differences between Examples 2 to 13 and Example 1 are shown in Table 1: Table 1 Parameter Comparison Table Comparative Example 1 The difference between this comparative example and Example 1 is that the median particle size D is directly increased. 50 LiNi, a ternary material with a thickness of 9.3 μm 0.8 Co 0.1 Mn 0.1 O2 was used to sinter the material at 500°C for 10 hours under an oxygen atmosphere. The sintered material was then sieved to obtain uncoated LiNi. 0.8 Co 0.1 Mn 0.1 O2 cathode material, and used to prepare lithium-ion batteries.

[0039] Comparative Example 2 The difference between this comparative example and Example 1 is that the median particle size D is directly increased. 50 The ternary material LiNi with a thickness of 4.9 μm 0.8 Co 0.1 Mn 0.1 O2 was used to sinter the material at 500°C for 10 hours under an oxygen atmosphere. The sintered material was then sieved to obtain uncoated LiNi. 0.8 Co 0.1 Mn 0.1 O2 cathode material, and used to prepare lithium-ion batteries.

[0040] Comparative Example 3 The difference between this comparative example and Example 1 is that the median particle size D is directly increased. 50 LiNi, a ternary material with a thickness of 6.5 μm 0.6 Co 0.1 Mn 0.3 O2 was used to sinter the material at 500°C for 8 hours under an oxygen atmosphere. The sintered material was then sieved to obtain uncoated LiNi. 0.8 Co 0.1 Mn 0.1 O2 cathode material, and used to prepare lithium-ion batteries.

[0041] The lithium-ion batteries of the above embodiments and comparative examples were tested: 1) High-temperature cycling performance test The lithium-ion batteries of the above embodiments and comparative examples were charged at 45°C with a constant current and constant voltage of 0.8C to 4.3V, with a cutoff current of 0.05C; then discharged at a constant current of 0.5C to 3.0V. The reversible capacity and coulombic efficiency of the batteries in the first cycle were calculated.

[0042] The battery was charged and discharged in the manner described above. After 500 charge-discharge cycles, the capacity retention rate of the battery in the 500th cycle was calculated. The corresponding test results for each lithium-ion battery are shown in Table 2.

[0043] 2) Ratio Test The lithium-ion batteries of the above embodiments and comparative examples were charged at 25°C at a rate of 0.5 and discharged at a rate of 0.5C for 10 cycles (0.5C / 0.5C); then charged at a rate of 0.5C and discharged at a rate of 1C for 10 cycles (0.5C / 1C); finally charged at a rate of 0.5C and discharged at a rate of 3C for 10 cycles (0.5C / 3C). The test results are shown in Table 2.

[0044] Table 2 Performance Test Table As shown in Table 2, compared with Comparative Example 1, Example 1 uses the ternary material LiNi in the positive electrode. 0.8 Co 0.1 Mn 0.1 Adding a small amount of Bi₂SeO₅ to O₂ forms a structurally stable coating layer on the surface of the ternary material after sintering. This prevents contact between the ternary material and the electrolyte, suppresses electrolyte decomposition and interfacial side reactions under high voltage, reduces the dissolution and release of ions from the ternary material surface, and improves the surface structure stability of the positive electrode active material. Furthermore, the high dielectric constant of Bi₂SeO₅ provides more effective electric field distribution control during battery charging and discharging, reducing polarization losses in the electrode material and improving the rate performance of the positive electrode active material. Therefore, the high-temperature cycling performance and discharge rate of the lithium-ion battery prepared in Example 1 are superior to those of Comparative Example 1. Similarly, Example 2 differs from Comparative Example 2 only in the ternary material LiNi 0.8 Co 0.1 Mn 0.1 The addition of Bi2SeO5 to O2 also resulted in the lithium-ion battery prepared in Example 2 having better high-temperature cycling performance and discharge rate than that of Comparative Example 2.

[0045] Compared with Example 1, Examples 2 to 4 changed the ternary material LiNi. 0.8 Co 0.1Mn 0.1 The median particle size D of O2 50 With LiNi 0.8 Co 0.1 Mn 0.1 The median particle size D of O2 50 With increasing particle size, the reversible capacity, coulombic efficiency, and discharge rate of various lithium-ion batteries gradually decrease in the first cycle, while the capacity retention rate after 500 cycles increases. This may be because as the ternary material particles increase in size, their specific surface area decreases, and the diffusion path of lithium ions in the electrode material becomes longer, thus reducing the diffusion rate of lithium ions and causing more lithium ions to fail to embed into the cathode material in time, resulting in a decrease in battery charging efficiency and capacity. Furthermore, at high discharge rates, the capacity decreases rapidly, and the coulombic efficiency also decreases. However, larger particle sizes can reduce the volume change of the ternary material during cycling, reduce stress concentration, and thus improve cycle stability, i.e., improve the capacity retention rate after 500 cycles.

[0046] Compared with Example 1, Examples 5 to 9 changed the amount of Bi2SeO5 added. With the increase of Bi2SeO5 added, the first-cycle reversible capacity, first-cycle coulombic efficiency, and discharge rate of the lithium-ion battery first increased and then decreased, while the capacity retention rate after 500 cycles continued to increase. The reason may be that when the amount of Bi2SeO5 added is small, it is not possible to form a sufficiently thick and stable coating layer, so it is difficult to prevent the contact between the ternary material and the electrolyte, and the suppression of electrolyte decomposition and interfacial side reactions under high voltage is weak. With the increase of Bi2SeO5 added, the thickness of the coating layer formed after sintering gradually increases, so it can effectively suppress electrolyte decomposition and interfacial side reactions under high voltage, and improve the high-temperature cycle performance and discharge rate of the lithium-ion battery. As the amount of Bi₂SeO₅ added continues to increase, the coating layer formed after sintering becomes too thick, leading to a longer diffusion path for lithium ions in the electrode material. This reduces the diffusion rate of lithium ions and prevents more lithium ions from being inserted into the cathode material in time, thus affecting the battery's charging efficiency, capacity, and coulombic efficiency. However, with the increase in coating layer thickness, the suppression of volume changes in the ternary material during cycling increases, thereby reducing stress concentration and improving cycle stability, i.e., improving the capacity retention rate after 500 cycles.

[0047] Compared with Example 1, Example 10 uses the ternary material LiNi 0.8 Co 0.1 Mn 0.1 O2 replaced with LiNi 0.6 Co 0.1 Mn 0.3O2 has a lower nickel content, which reduces its energy density. However, a lower nickel content results in a more stable structure, which may lead to better cycling stability during cycling.

[0048] Compared with Example 10, Example 11, and Example 13, compared with Example 12, reduced the LiNi 0.6 Co 0.1 Mn 0.3 O2 median particle size D 50 This leads to an increase in the reversible capacity, coulombic efficiency, and discharge rate of the lithium-ion batteries in Examples 11 and 13 during the first cycle, but a decrease in capacity retention after 500 cycles. The reason for this may be that as the ternary material particles decrease in size, their specific surface area increases, and the diffusion path of lithium ions in the electrode material becomes shorter, resulting in an increased lithium ion diffusion rate. This allows more lithium ions to be inserted into the cathode material in a timely manner, thus increasing the battery's charging efficiency and capacity. However, smaller particle sizes are not conducive to reducing the volume change of the ternary material during cycling and cannot reduce the stress concentration effect, resulting in poor cycle stability and a reduced capacity retention after 500 cycles.

[0049] Compared with Example 10, Example 12 and Example 13 compared with Example 11 have shortened sintering time, which is not conducive to the uniform forming of ternary materials and coating layers. Therefore, the performance of lithium-ion batteries in Examples 12 and 13 has decreased.

[0050] Compared with Comparative Example 3, Example 13 uses a ternary material LiNi at the positive electrode. 0.6 Co 0.1 Mn 0.3 Adding a small amount of Bi₂SeO₅ to O₂ allows for the formation of a structurally stable coating layer on the surface of the ternary material after sintering. This prevents contact between the ternary material and the electrolyte, thereby suppressing electrolyte decomposition and interfacial side reactions under high voltage, reducing the dissolution and release of ions from the ternary material surface, and improving the stability of the surface structure of the positive electrode active material. Furthermore, the high dielectric constant of Bi₂SeO₅ provides more effective electric field distribution control during battery charging and discharging, reducing polarization losses in the electrode material and improving the rate performance of the positive electrode active material. Therefore, the lithium-ion battery prepared in Example 13 exhibits superior high-temperature cycling performance and discharge rate compared to Comparative Example 3.

[0051] The above-described embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be included within the protection scope of the present invention.

Claims

1. A positive electrode material, characterized in that, It includes a core and a shell covering the core, the core comprising LiNi x M 1-x O2; wherein M is selected from at least two elements from Mn, Fe, Co, Ti, Y, Sc, Ru, Cu, Mo, Ce, W, Zr, Ca and P, and 0.3≤x<1; the shell material is Bi2SeO5; The core and the shell are inter-doped at adjacent interfaces to form an intermediate layer, the thickness of which is 0.5 nm to 200 nm. The thickness of the shell is 1nm~50nm; The diameter of the core is 2μm~20μm; The Bi₂SeO₅ content in the cathode material is 0.05% to 5% by mass. The method for preparing the cathode material includes the following steps: LiNi x M 1-x O2 material is mixed with Bi(NO3)3 material and selenium powder to obtain a mixed substance; The mixture is sintered to obtain the cathode material.

2. The cathode material according to claim 1, characterized in that, The Bi2SeO5 content in the cathode material is 0.1% to 2% by mass.

3. A positive electrode sheet, characterized in that, It includes a current collector and an active layer, the active layer being disposed on at least one side of the current collector, the active layer comprising the positive electrode material as described in any one of claims 1 to 2.

4. A lithium-ion battery, characterized in that, Includes the positive electrode sheet as described in claim 3.

Citation Information

Patent Citations

  • Lithium-rich manganese-based cathode material and preparation method thereof and lithium ion battery

    CN111640936A

  • Modified positive electrode material, preparation method thereof and all-solid-state lithium ion battery

    CN118039833A

  • Pre-lithiated silicon-carbon negative electrode material, preparation method and application

    CN118825229A

  • Positive electrode material and lithium secondary battery using the same

    US20190181448A1